TASMIMOPANAS : Modified Paper Using Waste of Pineapple as Purifier of Waste Cooking Oil - Salman Alfarisi; D. P. Mardiana; W. Pratiwi; Z. Khamidah (Tibuana, 2019)
Cooking oil was necessary of household to used when processed food ingridients. Waste cooking oil was contained free radicals can potentially oxidize organs. This problem overcome with rice straw and waste of pineapple which waste cooking oil was recycled by them. The utilization cellulose component on rice straw and waste of pineapple as natural active carbon can helped this problem. The absoption of subtances in waste cooking oil used paper from rice straw which heat together with Na2SO3 solvent while grinding processed with waste of pineapple to made pulp.